Cloud computing and security : second International Conference, ICCCS 2016, Nanjing, China, July 29-31, 2016, revised selected papers /: second International Conference, ICCCS 2016, Nanjing, China, July 29-31, 2016, revised selected papers. (2016) - Unknown
No abstract available